Mentalization and Reflective Functioning: Emergence and Development in clinical psychology - Fatemeh Abbasi,; Goodarzi, Mohammad Ali; Goodarzi, Mehdi Reza Sarafraz (International Journal of Psychosocial Rehabilitation, 2020)
This study is aimed to define and explore the emergence and development of mentalization and reflective functioning. Reflective functioning is referred to the psychological processes that are substantial for mentalizing. This is a review study. As results, mentalization and reflective functioning are different from other terms relating to understanding the mental states such as thoughts, feelings, desires or goals. Moreover, mentalization and reflective functioning are different as a matter of evaluating this characteristic. Deficit in mentalizing and reflective functioning results in fundamental interpersonal problems. Since mentalization or reflective functioning is a capacity that one is forming and developing from birth through the relationship with others and its deficit undermine the disturbances, it is crucial to be considered in research and clinical practice.